Mechanical Characterization and Modeling of Rat Myocardia under the Influence of Epirubicin - Alkhaiyat, Abdallah Mahmoud (AUC Knowledge Fountain, 2026)
Cancer remains a predominant health challenge that is responsible for a significant portion of global morbidity and mortality. Epirubicin (EPI), a chemotherapeutic anti-cancer drug, has shown remarkable efficacy in combating various malignancies. However, it is known to have undesirable side effects on the heart, collectively referred to as cardiotoxicity. This research investigates the adverse effects of chemotherapy on cardiac contractility through an in vitro examination of the mechanics of healthy and infarcted animal heart tissues. Electrically stimulated slices of rat ventricular tissue were tested using an isometric force measurement tissue bath. The tissue slices were subjected to uniaxial stretching, allowing the measurement of both active and passive tensions at varying preload levels. The uniaxial tension data were utilized to determine the stress-strain response of the tissue material. Subsequently, a hyperelastic constitutive model was fitted to the stress-strain data, providing us with material parameters for both healthy and infarcted cardiac tissues. Additionally, optical flow, a non-contact imaging technique, was employed to measure tissue specimen deformation during contraction. This process computes the deformation gradient of the tissue, ultimately enabling us to derive the full-field strain. The results show statistically significant evidence that EPI reduces the active tension by up to 71.7%. Similarly, there was statistically significant evidence that the passive tension was different between the two groups. Additionally, material calibration revealed that EPI increased the stiffness of the myocardium. Further results indicate a reduction in the magnitude of the myocardial strain after EPI administration. These findings indicate that EPI impairs cardiac contractility substantially, which is quantified by the reduction in active tension and myocardial strain. The observed increase in tissue stiffness, evident by the constitutive modeling, further confirms the notion of compromised contractility of the myocardium.